Heterochromatin loss as a determinant of progerin‐induced DNA damage in Hutchinson–Gilford Progeria. Issue 3 (22nd February 2020) - Chojnowski, Alexandre; Ong, Peh Fern; Foo, Mattheus Xing Rong; Liebl, David; Hor, Louis‐Peter; Stewart, Colin L.; Dreesen, Oliver
Abstract: Hutchinson–Gilford progeria is a premature aging syndrome caused by a truncated form of lamin A called progerin. Progerin expression results in a variety of cellular defects including heterochromatin loss, DNA damage, impaired proliferation and premature senescence. It remains unclear how these different progerin‐induced phenotypes are temporally and mechanistically linked. To address these questions, we use a doxycycline‐inducible system to restrict progerin expression to different stages of the cell cycle. We find that progerin expression leads to rapid and widespread loss of heterochromatin in G1‐arrested cells, without causing DNA damage. In contrast, progerin triggers DNA damage exclusively during late stages of DNA replication, when heterochromatin is normally replicated, and preferentially in cells that have lost heterochromatin. Importantly, removal of progerin from G1‐arrested cells restores heterochromatin levels and results in no permanent proliferative impediment. Taken together, these results delineate the chain of events that starts with progerin expression and ultimately results in premature senescence. Moreover, they provide a proof of principle that removal of progerin from quiescent cells restores heterochromatin levels and their proliferative capacity to normal levels. Abstract : Hutchinson–Gilford progeria is an accelerated aging syndrome caused by a truncated mutant form of lamin A, called progerin. Progerin expression results in rapid and widespread heterochromatin loss in G1‐arrested cells, without causing any DNA damage. Removal of progerin from G1‐arrested cells restores heterochromatin levels and leaves no permanent growth defect. Importantly, progerin‐induced DNA damage occurs exclusively in late S‐phase and preferentially in cells with low heterochromatin.